Integration of Carbon Trading and Indigenous Peoples’ Knowledge for Food Security and Sustainable Development in Central Kalimantan - Akbar, Wahyu; Setiawan, Rahmad Fahreza; Mar, Ma Tin Cho; Mirawati, Mirawati (OECONOMICUS Journal of Economics, 2025)
This paper investigates the integration of carbon trading with the indigenous knowledge of the Dayak community in Central Kalimantan as a strategy to enhance food security and bridge development disparities. Given the severe environmental and health risks posed by high carbon dioxide (CO2) emissions, mainly from industrial activities, this topic is crucial for balancing economic growth with ecological sustainability in a region facing significant climate change and economic inequality challenges. The research employs a descriptive-qualitative approach, using an extensive literature review to explore the synergy between carbon trading mechanisms and traditional forest management practices. The study analyzes data on carbon trading, indigenous practices, and their combined impact on environmental conservation and community welfare in Central Kalimantan. The study finds that integrating carbon trading with the Dayak community's indigenous forest management practices can significantly reduce greenhouse gas emissions, preserve biodiversity, and enhance the economic well-being of local populations. This integration aligns with Islamic financial principles, emphasizing the balanced and sustainable use of natural resources. The findings suggest that this model can effectively improve food security, reduce development disparities, and support inclusive and sustainable development in Central Kalimantan. The insights gained from this study provide valuable guidance for policymakers addressing environmental and socio-economic challenges in regions vulnerable to climate change